Sentence intonation in textual context - supplementary data - Grønnum Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1986)
The experiments presented here follow up a previous investigation (Nina Grønnum Thorsen "Intonation and text in Standard Danish", J. Acoust. Soc. Am. 77, 1985, 1205-1216) and were designed to show whether a sequential fundamental frequency lowering of individual sentence components is present in a semantically, but not syntactically, coherent sequence (a text), when the number of sentences exceeds three. The results show that such a sequential lowering may appear, though it is not evenly distributed across the text. However, the textual intonation contour is sensitive, not only to the number of sentences that make up the text, but also to the length of individual sentence components.